PERAN MAHASISWA KKN UNIVERSITAS BORNEO TARAKAN DALAM MENCEGAH STUNTING DAN GEMAR MAKAN IKAN DI DESA SENGKONG KECAMATAN SESAYAP HILIR KABUPATEN TANA TIDUNG - Prasetia, Abdul Muis; Hidaya, Nurman; Sartika, Linda; Soba, Andi Dian Lasarasi; Handayani, Fitri; Virgasha, Megasyafira Fajra; Riska, Ade; Nurholifah, Siti (Universitas Borneo Tarakan, 2024)
Stunting is a description of chronic malnutrition during growth and development from early life. Many factors can cause stunting in toddlers, such as toddler characteristics and socio-economic factors. This observational research was conducted in Sengkong Village, Sesayap Hilir District, Tana Tidung Regency. There is a lack of knowledge among village residents about stunting, so KKN students at the University of Borneo, Tarakan, collaborate with the village Community Health Center to carry out stunting prevention health education activities. This activity contains information about preventing and handling stunting appropriately. Then there is the impact of inequality that occurs if you do not implement a healthy and clean lifestyle which can cause stunting in children. Apart from that, KKN 01 UBT students also participated in providing appropriate, cheap complementary breast milk food to the residents of Sengkong Village. From this activity, the results and targets that KKN students want to achieve are citizens who have high enthusiasm so that this health education activity runs smoothly. Village residents no longer feel strange and know about how to prevent stunting. As well as, providing appropriate complementary foods for breast milk.